THEORETICAL AND METHODOLOGICAL PRINCIPLES OF RESOURCE MANAGEMENT IN THE MANAGEMENT SYSTEM OF INDUSTRIAL ENTERPRISES - NAZARCHUK, Tetiana; BAKAI, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the theoretical and methodological foundations of resource management within the management systems of industrial enterprises. The study investigates the essential aspects of resource provision, its structural components, and different management levels. A detailed analysis is conducted on the primary methods and tools for optimizing the use of material, financial, human, technological, and informational resources. The research highlights the necessity of a comprehensive approach to resource management, considering contemporary challenges such as globalization, rapid technological advancements, and market volatility.A structured and logical model for resource management is proposed, integrating strategic, tactical, and operational levels. The study emphasizes the importance of implementing modern management techniques, including digital transformation, automation, and innovative development strategies, to enhance resource efficiency. Additionally, practical recommendations are provided for industrial enterprises to optimize their resource allocation, improve production processes, and strengthen their competitive positions in the global market.The findings suggest that an effective resource management system contributes to increased productivity, reduced operational costs, and sustainable industrial growth. The article also discusses the role of environmental and social responsibility in resource management, highlighting the necessity for enterprises to adopt sustainable and eco-friendly practices. Future research directions include further exploration of digital transformation’s impact on resource management, the development of adaptive models for enterprises in dynamic environments, and the advancement of performance evaluation methods for resource efficiency.
Keywords: management; management system; resource provision; resource management; industrial enterprise; planning; efficient use of resources